Liquid metal corrosion : fundamental theory and applications - Zhang, Jinsuo (Woodhead Publishing, an imprint of Elsevier, 2023)
"Liquid Metal Corrosion: Fundamental Theory and Applications is designed to help scientists, engineers and students working on liquid metal (sodium, lead, lead-bismuth) to fundamentally understand liquid metal corrosion. Coverage includes a discussion of corrosion mechanisms, fundamental corrosion processes, and corrosion products' behaviors as well as methods on how to calculate corrosion rates. The book concludes with models designed to predict the corrosion/precipitation distribution in a primary corrosion loop. This book will be a useful resource for researchers in their efforts to determine appropriate materials selection and reactor design." -- Provided by publisher.
Keywords: Liquid metals -- Corrosion.; elektronické knihy; electronic books